CREATING A SUSTAINABLE DIGITAL BUSINESS ECOSYSTEM: CHALLENGES AND OPPORTUNITIES FOR GLOBAL ECONOMIC DEVELOPMENT - Arifin, Ahmad (STKIP Persada Khatulistiwa Sintang, 2024)
This research aims to analyze the challenges and opportunities in creating a sustainable digital business ecosystem to support inclusive global economic growth. The research method used includes collecting and analyzing various documents such as research reports, academic publications, government policies, and industry documents related to digital business ecosystems, sustainability, and global economic development. The results show that the integration between the concepts of digital business ecosystems and sustainability has a crucial role in creating a sustainable business environment. Key factors such as digital inclusion, sustainable innovation and multi-stakeholder partnerships were identified as important elements in achieving this goal. The implications of this research highlight the need for collaborative action between governments, companies, and non-governmental organizations in designing policies and business practices that support sustainable economic growth. Building a comprehensive, forward-thinking, and environmentally friendly digital business network is essential for long-term economic development that positively impacts society. Stakeholders can achieve long-term improvements that benefit future generations by prioritizing economic, social, and environmental sustainability. This research aims to build a durable digital business environment for the betterment of the world economy through its contribution to academic literature and business practice.